Comparison of Pregnancy Outcomes with Autoimmune Rheumatic Disease and Without Autoimmune Rheumatic Disease - Sulaiman, Aina Zakia; Pribadi, Adhi; Hamijoyo, Laniyati; Irianti, Setyorini; Rahmadi, Andri Reza (Indonesian Journal of Obstetrics & Gynecology Science, 2024)
Introduction: It is known that pregnancies with autoimmunity have a higher risk of complications in the mother and fetus compared to pregnancies without autoimmunity. The purpose of this study was to determine the comparison between pregnancy outcomes with autoimmune rheumatic disease and without autoimmune rheumatic disease.Methods: This study is an observational analytic with a retrospective cross-sectional design. Data were obtained from all patients with pregnancy outcomes with autoimmune rheumatic disease and without autoimmune rheumatic disease at Hasan Sadikin Hospital Bandung 1 January - 31 December 2021-2023.Results: During this period, 71 pregnant women were found to be accompanied by autoimmune rheumatic diseases and then data on pregnant women without autoimmune rheumatic diseases were randomly taken as controls. In this study, it was found that pregnant women with autoimmune diseases experienced more neonatal outcomes of stunted fetal growth, namely 11(15.5%) compared to pregnant women without autoimmune rheumatic diseases, namely 2(2.8%) with a p-value of 0.009.Conclusion: This study found that pregnant women with autoimmune rheumatic disease experienced more neonatal outcomes of FGR compared to pregnant women without autoimmune rheumatism.Perbandingan Antara Luaran Kehamilan Dengan Penyakit Rhematik Autoimun Dan Tanpa Penyakit Rematik AutoimunAbstrakPendahuluan: Diketahui bahwa kehamilan dengan autoimun memiliki risiko komplikasi pada ibu maupun janin lebih tinggi dibandingkan dengan kehamilan tanpa autoimun. Tujuan penelitian ini untuk mengetahui perbandingan antara luaran kehamilan dengan penyakit rematik autoimun dan tanpa penyakit rematik autoimunMetode: Penelitian ini bersifat analitik observasional dengan desain potong lintang retrospektif. Data diperoleh dari seluruh pasien luaran kehamilan dengan penyakit rematik autoimun dan tanpa penyakit rematik autoimun di Rumah Sakit Hasan Sadikin Bandung 1 Januari – 31 Desember 2021-2023Hasil: Dalam periode tersebut ditemukan 71 orang ibu hamil yang disertai dengan penyakit rematik autoimun kemudian diambil data ibu hamil tanpa penyakit rematik autoimun secara random sebagai kontrol. Pada penelitian ini didapatkan ibu hamil dengan penyakit autoimun lebih banyak mengalami luaran neonatal pertumbuhan janin terhambat yaitu 11(15.5%) dibandingkan ibu hamil tanpa penyakit rematik autoimun yaitu 2(2.8%) dengan p- value0.009.Kesimpulan : Penelitian ini menemukan bahwa ibu hamil dengan penyakit rematik autoimun lebih banyak mengalami luaran neonatal pertumbuhan janin terhambat dibandingkan dengan ibu hamil tanpa rematik autoimun.Kata kunci : Luaran Maternal, Luaran Neonatal, Autoimun